Numerical Study of Viscoelastic Microfluidic Particle Manipulation in a Microchannel with Asymmetrical Expansions - Tiao Wang; Dan Yuan; Wuyi Wan; Boran Zhang (Micromachines, 2023)
Microfluidic microparticle manipulation is currently widely used in environmental, bio-chemical, and medical applications. Previously we proposed a straight microchannel with additional triangular cavity arrays to manipulate microparticles with inertial microfluidic forces, and experimentally explored the performances within different viscoelastic fluids. However, the mechanism remained poorly understood, which limited the exploration of the optimal design and standard operation strategies. In this study, we built a simple but robust numerical model to reveal the mechanisms of microparticle lateral migration in such microchannels. The numerical model was validated by our experimental results with good agreement. Furthermore, the force fields under different viscoelastic fluids and flow rates were carried out for quantitative analysis. The mechanism of microparticle lateral migration was revealed and is discussed regarding the dominant microfluidic forces, including drag force, inertial lift force, and elastic force. The findings of this study can help to better understand the different performances of microparticle migration under different fluid environments and complex boundary conditions.